PROBLEMS OF URBANIZATION IN THE CONTEXT OF CREATING A COMFORTABLE URBAN ENVIRONMENT - N. Musinova (Вестник университета)
Urbanization, which changes the habitual living environment of people, in the process of its development leads to increased negative factors, affecting their livelihoods and health. A number of problems, associated with the development of cities: high population density, changes in insolation norms, lack of space for the formation of a comfortable urban environment, etc has been considered in the article. The attention has been focused on the fact, that the revision of such standards as insolation time, location of parking lots, etc., associated with the creation of compact cities, should be balanced.